A new concept of monolithic silicon pixel detectors: hydrogenated amorphous silicon on ASIC - Anelli, G.; Commichau, S. C.; Despeisse, M.; Dissertori, G.; Jarron, P.; Miazza, C.; Moraes, D.; Shah, Arvind; Viertel, G. M.; Wyrsch, Nicolas (My University, 2004)
A new concept of a monolithic pixel radiation detector is presented. It is based on the deposition of a film of hydrogenated amorphous silicon (a-Si:H) on an Application Specific Integrated Circuit (ASIC). For almost 20 years, several research groups tried to demonstrate that a-Si:H material could be used to build radiation detectors for particle physics applications. A novel approach is made by the deposition of a-Si:H directly on the readout ASIC. This technique is similar to the concept of monolithic pixel detectors, but offers considerable advantages. We present first results from tests of a n–i–p a-Si:H diode array deposited on a glass substrate and on the a-Si:H above ASIC prototype detector.
Keywords: metrology; solid state detectors